Medical record analysis in supporting bpjs health claims in a hospital: A retrospective descriptive quantitative study - Wa Ode Novi Angraeni; Jessy Andre Mangaya Takke; NurZetty Sofia Zainuddin (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2026)
Introduction: Delays in inpatient BPJS Health claims represent a persistent operational challenge within Indonesia’s National Health Insurance (JKN) system and may compromise hospital financial stability under case-based reimbursement (INA-CBGs). Inefficiencies are frequently attributed to incomplete medical documentation and weak integration with health information systems. This study aimed to analyze the role of the Hospital Management Information System (HMIS), medical record completeness, and coding accuracy in determining inpatient BPJS claim pending status at a tertiary teaching hospital. Research Methodology: An analytical cross-sectional study with retrospective document review was conducted at Hasanuddin University Hospital from November to December 2025. A total of 156 inpatient BPJS claim files for May 2025 were included using total sampling. Data were extracted from casemix records, HMIS databases, and medical documentation. Bivariate associations were tested using chi-square analysis, and multivariate predictors were identified through binary logistic regression (α = 0.05). Results: Of 156 claims, 66.7% were classified as pending. Incomplete medical records (AOR = 9.84; 95% CI: 3.21–30.18; p < 0.001), HMIS data non-conformity (AOR = 8.92; 95% CI: 3.45–23.06; p < 0.001), and coding inaccuracies (AOR = 6.17; 95% CI: 1.78–21.42; p = 0.004) were independently associated with increased odds of pending claims. Conclusion: Inpatient BPJS claim delays are primarily driven by weaknesses in documentation governance and digital system integration. Strengthening standardized clinical documentation, enhancing coder competency, and improving HMIS interoperability are critical to reducing claim discrepancies, improving reimbursement efficiency, and supporting the financial sustainability of Indonesia’s National Health Insurance system